The Character Value Education Analysis in Pakpak Folklore on Indonesian Language Learning - Ceing Suwarni; Rosliani Rosliani (Budapest International Research and Critics University, 2020)
The convenience provided by internet technology causes students to be lazy about reading books and prefer to access them through search engines. Students also care less about the environment. In addition, the negative impact caused is decreased student discipline. This study aims to describe the value of the folklore characters in the book